Climate Changes and their Effects on Changing the Green Bean Crop in Wasit Governorate a Research in Physical Geography - محمد كريم جنيط م. د. (lark, 2021)
The research revealed the analysis of climatic changes and their effects on the change of the green bean crop in Wasit Governorate. To show the effects of those global climatic changes that affected the change of climatic elements in Wasit Governorate, and their impact on the green bean crop, for the period (1986-2018). The general trend factor adjusted for the number of actual hours of sunshine tends to decrease. The general trend factor for the minimum and maximum temperatures tends to rise in the studied stations. The general trend factor for the annual rate of the amount of rainfall tends to rise in the stations (Baghdad and Hilla) and towards the decrease in the stations (Al- Hayy and Al- Diwaniyah). These changes have a role in influencing plant life, affecting the yield of green beans in the Wasit Governorate.